2021
DOI: 10.3389/fimmu.2021.698249
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Extracellular Traps Exacerbate Secondary Injury via Promoting Neuroinflammation and Blood–Spinal Cord Barrier Disruption in Spinal Cord Injury

Abstract: As the first inflammatory cell recruited to the site of spinal cord injury (SCI), neutrophils were reported to be detrimental to SCI. However, the precise mechanisms as to how neutrophils exacerbate SCI remain largely obscure. In the present study, we demonstrated that infiltrated neutrophils produce neutrophil extracellular traps (NETs), which subsequently promote neuroinflammation and blood–spinal cord barrier disruption to aggravate spinal cord edema and neuronal apoptosis following SCI in rats. Both inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 39 publications
0
32
0
1
Order By: Relevance
“…We considered that the high heterogeneity is due to differences in the extent of injury, measurement methods, and baseline conditions in rats across studies. All treatments, except one ( Feng et al, 2021 ), had statistically significant positive effects, indicating that the included treatment regimens had a positive effect on mitigating BSCB destruction. The forest plot showed that Xin et al (2021) had the greatest reduction (90%) in EB leakage, treated with BMSC-Exos.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…We considered that the high heterogeneity is due to differences in the extent of injury, measurement methods, and baseline conditions in rats across studies. All treatments, except one ( Feng et al, 2021 ), had statistically significant positive effects, indicating that the included treatment regimens had a positive effect on mitigating BSCB destruction. The forest plot showed that Xin et al (2021) had the greatest reduction (90%) in EB leakage, treated with BMSC-Exos.…”
Section: Resultsmentioning
confidence: 95%
“…We considered that the high heterogeneity is due to differences in the of injury, measurement methods, and baseline conditions in rats across studies. All treatments, except one (Feng et al, 2021), had statistically significant positive effects, 2019) treated with Protocatechuic acid (78%). These studies all achieved >70% reduction in EB leakage.…”
Section: Attenuation Of Blood Spinal Cord Barrier Breakdownmentioning
confidence: 96%
“…Previous research has shown that NETs induce inflammatory responses and damage the BSCB, resulting in axonal degeneration, which is not conducive to neuronal regeneration. The arginine deaminase-4 peptide blocks the formation of NETs by DNAse-1, which reduces cell death and scar formation, thereby promoting functional recovery ( Feng et al, 2021 ). In addition, NETs accelerate endothelial cell injury and destroy the BSCB by increasing the expression of TRPV4.…”
Section: Immune Cells In the Microenvironment Of Spinal Cord Injurymentioning
confidence: 99%
“…The activation of neutrophil PRRs by locally-produced DAMPs (171) results in a dramatic upregulation of pro-inflammatory cytokines, proteases and tissue-degrading enzymes, overall contributing to a harmful tissue environment (172). More recently, one study highlighted the detrimental effect of NETs formation in a clip-compression SCI model (173). Infiltrating neutrophils at lesion sites in the spinal cord release NETs, as measured by dsDNA dye Sytox, CitH3, and MPO staining, exacerbating both secondary fibrotic scar formation and the disruption of blood-spinal cord barrier, promoted by an increased endothelial expression of the transient receptor potential vanilloid type 4 (TRPV4), a calcium-permeable nonselective cation channel.…”
Section: Spinal Cord Injurymentioning
confidence: 99%